"Their Whole Lives Are Going To Change": A Photo-Elicitation Study of Rectal Cancer Survivorship. Issue 12 (15th November 2022) - Rivard, Samantha J.; Vitous, C. Ann; Bamdad, Michaela C.; Varlamos, Christopher; Duby, Ashley; Suwanabol, Pasithorn A.
Abstract : BACKGROUND: Rectal cancer survivors experience persistent symptoms, which may lead to unmet needs. OBJECTIVE: This study aimed to explore the rectal cancer survivor experience and identify the impacts of treatment using photo-elicitation. DESIGN: This was a novel study in which patients were instructed to take photographs that showed aspects of life that have been challenging to deal with since undergoing treatment. Participants underwent subsequent qualitative interviews using the photographs as prompts. SETTING: The study was conducted in a cancer center in a tertiary medical center. PATIENTS: Twenty patients were included who underwent curative-intent rectal cancer treatment. MAIN OUTCOME MEASURES: Interviews were designed to explore the lived experiences of patients with rectal cancer after treatment. RESULTS: Three major themes with regard to life after rectal cancer and its treatments emerged: physical symptoms, lifestyle changes, and changes over time. Physical symptoms encompassed GI issues, ostomy difficulties, and genitourinary symptoms. Lifestyle changes included those relating to diet, social life, and hobbies as well as major life changes and finances. Finally, patients spoke of improvement during the time of symptoms and impact on daily life. LIMITATIONS: There may be bias because of the homogeneity of our study population, which may not represent the experiences of younger patients, those of lower socioeconomic status, or those who chose not to participate. Our sample was also overrepresented by patients with a complete pathologic response after neoadjuvant chemotherapy and excluded individuals with recurrence. Finally, single interviews with each individual at different points from their treatment may have resulted in recall bias. CONCLUSIONS: This photo-elicitation study provided rectal cancer survivors with a unique opportunity to share how rectal cancer treatment has impacted their lives beyond traditional metrics such as postoperative complications and long-term survival. In addition to improving preoperative counseling and expectation setting, future efforts should focus on postoperative symptom surveillance and appropriate referral when needed. See Video Abstract at http://links.lww.com/DCR/C7 . "SUS VIDAS ENTERAS VAN A CAMBIAR": UN ESTUDIO DE OBTENCIÓN DE IMÁGENES SOBRE LA SUPERVIVENCIA AL CÁNCER DE RECTO: ANTECEDENTES: Los sobrevivientes de cáncer de recto experimentan síntomas persistentes, lo que puede dar lugar a necesidades no satisfechas. OBJETIVO: Explorar la experiencia de los sobrevivientes de cáncer de recto e identificar los impactos del tratamiento mediante el uso de fotoestimulación. DISEÑO: En este nuevo estudio, se instruyó a los pacientes para que tomaran fotografías que mostraran aspectos de la vida que han sido difíciles de manejar desde que se sometieron al tratamiento. Los participantes se sometieron posteriormente a entrevistas cualitativas utilizando las fotografías como estimuladores. ESCENARIO: Centro oncológico en un centro médico terciario. PARTICIPANTES: Veinte pacientes que se sometieron a tratamiento de cáncer de recto con intención curativa. PRINCIPALES MEDIDAS DE RESULTADO: Las entrevistas se diseñaron para explorar las experiencias vividas por los pacientes con cáncer de recto después del tratamiento. RESULTADOS: Surgieron tres temas principales con respecto a la vida después del cáncer de recto y sus tratamientos: síntomas físicos; cambios en el estilo de vida; y cambios en el tiempo. Los síntomas físicos abarcaron problemas gastrointestinales, dificultades de las ostomías y síntomas genitourinarios. Los cambios en el estilo de vida incluyeron aquellos relacionados con la dieta, la vida social y los pasatiempos, así como cambios importantes en la vida y las finanzas. Por último, los pacientes hablaron de una mejoría con el tiempo de los síntomas y el impacto en la vida diaria. LIMITACIONES: Puede haber sesgo debido a la homogeneidad de nuestra población de estudio, que puede no representar las experiencias de los pacientes más jóvenes, los de nivel socioeconómico más bajo o los que optaron por no participar. Nuestra muestra también estuvo sobrerrepresentada por pacientes con una respuesta patológica completa después de la quimioterapia neoadyuvante y excluyó a los individuos con recurrencia. Finalmente, las entrevistas individuales con cada paciente en diferentes puntos de su tratamiento pueden dar lugar a que los participantes experimenten un sesgo de recuerdo. CONCLUSIONES: Este estudio de obtención de fotografías brinda a los sobrevivientes de cáncer de recto una oportunidad única de compartir cómo el tratamiento del cáncer de recto ha impactado sus vidas más allá de las métricas tradicionales, como las complicaciones posoperatorias y la supervivencia a largo plazo. Además de mejorar el asesoramiento preoperatorio y el establecimiento de expectativas, los esfuerzos futuros deben centrarse en la vigilancia de los síntomas posoperatorios y la derivación adecuada cuando sea necesario. Consulte Video Resumen en http://links.lww.com/DCR/C7 .